HUBUNGAN PENGETAHUAN DENGAN KESIAPSIAGAAN SISWA DALAM MENGHADAPI BENCANA - Yayat Supriyatna; Ni Putu Sinta Puspa Dewi; Sri Rahayu (Akademi Kebidanan Harapan Bunda Bima, 2026)
Disasters are events that can threaten human life and cause physical, psychological, and environmental impacts. Indonesia, including Central Kalimantan, is one of the regions vulnerable to disasters such as floods, forest and land fires, and extreme weather. Lack of disaster preparedness among students can increase the risk of panic, injury, and inappropriate response during emergency situations at school. Therefore, knowledge about disaster preparedness is important to improve students’ readiness in facing disasters. This study aimed to determine the relationship between knowledge and students’ preparedness in facing disasters at a senior high school in Central Kalimantan. This research used a quantitative design with a cross sectional approach. The study was conducted in February 2026 involving 60 respondents selected using simple random sampling. Data were collected using knowledge and disaster preparedness questionnaires. Data analysis was performed using univariate and bivariate analysis with the Spearman Rank test. The results showed that most respondents had good knowledge (53.3%) and were categorized as prepared in facing disasters (63.3%). Statistical analysis showed a significant relationship between knowledge and disaster preparedness with a p-value of 0.001 (<0.05). Students with better knowledge tended to have higher preparedness in dealing with disaster situations. The study concludes that knowledge has an important role in improving students’ disaster preparedness. Continuous disaster education and simulation programs are needed to support disaster-resilient schools and improve students’ readiness in emergency situations.